Demonstratie tegen verkiezingsbijeenkomst NVU in hotel Carnegie. De politie arresteert 2 mensen - Singels, Han (1977)
Demonstratie tegen verkiezingsbijeenkomst NVU in hotel Carnegie. De politie arresteert 2 mensen.